2020
DOI: 10.1016/j.chembiol.2019.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Polycomb Repressive Complex 2 with an EED-Targeted Bivalent Chemical Degrader

Abstract: Protein degradation via the use of bivalent chemical degraders provides an alternative strategy to block protein function and assess the biological roles of putative drug targets. This approach capitalizes on the advantages of small-molecule inhibitors while moving beyond the restrictions of traditional pharmacology. Here, we report a chemical degrader (UNC6852) that targets polycomb repressive complex 2 (PRC2). UNC6852 contains an EED226derived ligand and a ligand for VHL which bind to the WD40 aromatic cage … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(122 citation statements)
references
References 53 publications
2
114
0
1
Order By: Relevance
“…It is well documented that the identification of appropriate vectors from the warhead and anchor is critical to devise a suitable strategy for their conjugation to the linker and access potent degraders [128]. The availability of high-resolution co-crystal structures for warheads bound to the POIs is an invaluable tool and often a prerequisite for PROTAC design and assembly, in particular to identify solvent-exposed exit vectors on the warhead where a linker can be conjugated with minimal effect on POI binding [129][130][131][132]. As an illustrative example, Maniaci et al [133], utilised the co-crystal structure (PDB 5LLI) of VHL in complex with VH298 (87) for the development of "Homo-PROTACs" for the self-induced degradation of VHL.…”
Section: Exploiting X-ray Crystal Structures Of Protein/ligand Binarymentioning
confidence: 99%
“…It is well documented that the identification of appropriate vectors from the warhead and anchor is critical to devise a suitable strategy for their conjugation to the linker and access potent degraders [128]. The availability of high-resolution co-crystal structures for warheads bound to the POIs is an invaluable tool and often a prerequisite for PROTAC design and assembly, in particular to identify solvent-exposed exit vectors on the warhead where a linker can be conjugated with minimal effect on POI binding [129][130][131][132]. As an illustrative example, Maniaci et al [133], utilised the co-crystal structure (PDB 5LLI) of VHL in complex with VH298 (87) for the development of "Homo-PROTACs" for the self-induced degradation of VHL.…”
Section: Exploiting X-ray Crystal Structures Of Protein/ligand Binarymentioning
confidence: 99%
“…Many studies have shown that PROTACs are not entirely selective and can degrade proteins other than the primary target (Bai et al, ; Bondeson et al, ; Brand et al, ; Matyskiela et al, ; Yang et al, ; Zorba et al, ). Degradation of a protein that is not directly bound by the PROTAC can arise as a consequence of “bystander degradation” where the degradation of a protein that is not directly bound by the PROTAC becomes ubiquitinated and hence degraded as part of the same complex with the PROTAC POI (Hsu et al, ; Maniaci et al, ; Potjewyd et al, ). In other instances, this is an off‐target effect due to the neo‐morphic interactions with so‐called neosubstrates, which become ubiquitinated by the E3 ligase and subsequently degraded (Figure ).…”
Section: Safety Challenges For Protacsmentioning
confidence: 99%
“…In 2020, two separate research groups successfully converted the EED inhibitors into PROTACs [47,161]. Interestingly, both groups used the VHL ligand to design the PROTACs, but used different EED inhibitors as the warhead, as well as different strategies for linker optimization.…”
Section: Prc2mentioning
confidence: 99%
“…The most potent compound named PROTAC2 developed by Bloecher’s group selectively degraded EED, EZH2, and SUZ12, and reduced the proliferation of EZH-dependent tumor cells Karpas422 [ 161 ]. The most potent compounds named UNC6852 developed by James’ group also selectively degraded EED, EZH2, and SUZ12, and potently inhibited the proliferation of DLBCL cell lines with a wild-type and Y641N mutant EZH2 [ 47 ]. Although the EED-based PROTACs could degrade EZH2, so far no selective PROTACs based on EZH2 inhibitors were reported, until 2019 when Jian et al developed MS1943, an EZH2 inhibitor-based degrader, via hydrophobic tagging strategy, which was designed by linking an EZH2 inhibitor to a bulky adamantyl group [ 162 ].…”
Section: Protacs Against Hematologic Malignanciesmentioning
confidence: 99%